Analyzing and evaluating the service quality of foreign banks’ digital offerings in China: a case study of online banking and mobile banking - GUO, YIFEI (2017)
The purpose of this article is to explore the overall performance of the three selected foreign banks’ service quality in digital offerings (online banking and mobile banking) in Chinese retail banking context. The three sample banks were selected based upon accessibility. They are HSBC from UK, Citibank from USA and UOB from Singapore. The service qualities of the banks’ digital platforms were thoroughly examined by adopting a methodology that combines two measurement models known as SERVQUAL and SERVPERF, and seven specific e-BSQ dimensions which are competence, ease-of-use, service variety, reliability, responsiveness, security and awareness. The 3-week field survey, with 313 valid questionnaires competed, was conducted amongst the web-banking and m-banking customers. The findings also indicated that most customers were unaware of their banks digital service functions. They only knew several basic, free and widely-used functions such as balance inquiries, mobile payments and real-time fund transfers. By comparing the three bank’s survey results, insightful information like customer perceptions of service quality and the three banks’ differences in terms of their services and quality, can guide the web-banking and m-banking service providers to improve the effectiveness and efficiency of their digital offerings, and thereby effectively increase the satisfaction and loyalty of the customers. As web-banking and m-banking are electronic platforms which provide services remotely, the empirical findings of this project may also contribute to other distance services or electronic services such as telephone banking.